Kearifan Lokal Perguruan Tinggi Menghadapi Liberalisasi Pendidikan - Djohar MS (Unisia, 2006)
The presenting of foreign universities in Indonesia will become an Interesting and challenge phenomenon. If this happens, many Indonesian people will enter the foreign universities although the education cost expensive because of the advancing or development. In thsis sense, the academic institutions denote comercial institution. Hence, the image of the scientificity tends to become unclear, on one hand Indonesia has the institution to develop science and technology, and on the other Indonesia does not pay attention to sicence and technology. The liberalization of education implies to Indonesian system of education which each institution moves based on its interest.